Polarization selective antennas for reflected wave depolarization determination - Averyanova, Yu. A.; Yanovsky, F. J.; Averyanov, A. A. (Видавництво Національного університету "Львівська політехніка", 2009)
In this paper the approach to estimate dynamic processes in the atmosphere with help of polarimetry as well as multi-antenna polarimetric radar system is considered. The requirements to polarization selective antennas parameters are discussed.
Keywords: radar polarimetry; polarization antennas; atmospheric dynamics